SYSTEMATIC LITERATUR REVIEW: MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI BANGUN - Amrina Rosada; Maria Luthfiana (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2022)
The purpose of this research is to review the articles on mathematics learning on the material of building space using the Contextual Teaching and Learning model. This research method uses literature review, namely library research (Library Research) namely SLR or (Systematic Literature Review) by collecting data from several relevant journals. This study analyzes 5 relevant mathematical journals regarding the CTL model in mathematics learning on the material of spatial structure. Based on the analysis of the 5 journals, it can be concluded that learning mathematics using the CTL model in building materials can improve student learning outcomes.